Model Pengembangan Media Alat Peraga Tradisional untuk Meningkatkan Aktivitas Fisik Siswa Sekolah Dasar di Parepare - Marhani Marhani (ARZUSIN, 2026)
Although instructional media and physical-activity-based approaches have been widely examined, the development of traditional instructional aids that are systematically integrated into Pendidikan Jasmani, Olahraga, dan Kesehatan (Physical Education, Sports, and Health, PJOK) instruction to increase physical activity among elementary school students remains relatively limited. This study aimed to develop and test the effectiveness of a traditional instructional media model in enhancing the physical activity of elementary school students in Parepare. A quantitative approach was employed using a Research and Development (R&D) method combined with a one-group pretest–posttest quasi-experimental design. The research subjects consisted of 60 fourth- and fifth-grade students selected through purposive sampling. Data were collected using expert validation sheets, physical activity observation instruments, and student response questionnaires, and were analyzed using descriptive statistics and paired-samples t-tests. The findings showed that the model developed through the integration of traditional games such as engklek, gobak sodor, and egrang into PJOK learning scenarios obtained an average expert validation score of 91.4%, categorized as very valid. The students’ mean physical activity score increased significantly from 62.35 at pretest to 83.70 at posttest, representing an increase of 21.35 points (34.24%), with statistical testing indicating a significant difference between pretest and posttest scores (t = 9.87; p < 0.001). In addition, 88% of students demonstrated high levels of engagement and enthusiasm during instruction. These findings contribute to strengthening culturally responsive pedagogy and active learning theories, and broaden the understanding of contextual PJOK instructional practices in elementary schools. The study concludes that the integration of traditional instructional aids plays an important role in increasing students’ physical activity and learning motivation, and recommends that PJOK teachers and schools adopt locally rooted, culture-based instructional media as an innovative instructional strategy, while encouraging further research with wider implementation scales and longer durations.